PENGARUH FLEKSIBILITAS KERJA DAN KOMPENSASI TERHADAP KINERJA DRIVER SHOPEEFOOD DI KOTA SEMARANG DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING - Assiddiqy, Muchammad Najmi; Setyorini, Noni; Setiawati, Ira (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This study aims to determine the effect of work flexibility and compensation on the performance of Shopeefood drivers in Semarang City, with work motivation as an intervening variable. The method used in this study is quantitative, utilizing primary data with a questionnaire collected from 96 Shopeefood driver respondents. Hypothesis testing used the Structural Equation Model (SEM) method with the assistance of SmartPLS software. The results of this study prove that: (1) Work flexibility has a significant effect on work motivation (2) Compensation has a significant effect on work motivation (3) Work flexibility has a significant effect on performance (4) Compensation has no significant effect on performance (5) Work motivation has a significant effect on performance (6) Work flexibility has a significant effect on performance through work motivation as an intervening variable (7) Compensation has no significant effect on performance through work motivation as an intervening variable